2004
DOI: 10.1021/ja0484404
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Supramolecular Assembly, and Nanostructures of Thiophene Dendrimers

Abstract: We report the synthesis and characterization of dendritic thiophene derivatives with their unique supramolecular assembly into 2-D crystals, nanowires, and nanoparticle aggregates. The structure and size of the dendrons and dendrimers have been confirmed with various techniques, such as NMR, SEC, and MALDI-TOF-MS. The mass values were consistent with the mass observed by MALDI-TOF-MS, whereas SEC measurements also gave useful information on the hydrodynamic volume of the individual dendrimers. The interesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 39 publications
2
134
0
2
Order By: Relevance
“…Advincula and co-workers have developed thiophene-based dendrimers and showed that these compounds present broad absorption and narrow fluorescence spectra. [70] Ponomarenko et al have reported OFETS based on dendritic structures containing quaterthiophene chains (52). [71] The devices made by spin-coat- (53,54) have been used as donor.…”
Section: Wwwadvmatde 2055mentioning
confidence: 99%
“…Advincula and co-workers have developed thiophene-based dendrimers and showed that these compounds present broad absorption and narrow fluorescence spectra. [70] Ponomarenko et al have reported OFETS based on dendritic structures containing quaterthiophene chains (52). [71] The devices made by spin-coat- (53,54) have been used as donor.…”
Section: Wwwadvmatde 2055mentioning
confidence: 99%
“…1). [15] The authors studied the self-organization properties of these molecules on different substrates and showed their ability to form nanostructures on surfaces, which has great potential for applications in organic electronics. A calixarene±quaterthio-phene-based polymer that became highly conductive upon protonation was prepared by H. Yu et al [34] A Stille coupling between di-iodocalixarene and the monostannyl derivative of 2,2¢-bithiophene afforded the monomeric unit which was then electropolymerized (F, Fig.…”
Section: Synthesismentioning
confidence: 99%
“…[2,3] A number of these conjugated polymer dendrimer systems are based on poly(phenylene ethynelenes), [4] polyphenylenes, [5] polythiophenes, [5,6] etc.…”
mentioning
confidence: 99%